Performance of landrace and improved rice varieties under the system of rice intensification management in Bajhang District of Nepal - Khadka, Ram B; Acharya, Hari P; Uphoff, Norman (Journal of Agriculture and Environment, 2014)
Participatory action research was conducted in Luinyata VDC of Bajhang district during main rice-growing season of 2012 to evaluate the effects of cultivation practices in rice varieties. The experiment was in factorial randomized complete block design, where two methods of cultivations: System of rice intensification (SRI) and conventional transplanting (CT) and 3 different varieties: Khumal-4, Thapachini and Hansaraj Basmati were evaluated. Data were collected on grain yield, number of tillers, panicle length and number of filled and unfilled grains per panicle. Results averaged across the three varieties showed significantly better crop performance with SRI practices: higher number of tillers per hill, panicles per hill, tillers per m2, panicles per m2, and grain yield. The values of these parameters comparing SRI with conventional practice were, respectively, 24.5 vs. 11.3, 21.5 vs. 9.5, 305 vs. 273, 273.5 vs. 233.8, and 7.6 vs. 4.46 tha-1. Among the varieties evaluated, the highest yield was achieved with the Thapachini (8.11tha-1) using SRI methods. Average yield increase across the three varieties with SRI practice was 70% compared CT. These results indicate the practical relevance of SRI principles for increasing rice production in mountainous regions of Nepal.